2020
DOI: 10.1108/pijpsm-06-2019-0087
|View full text |Cite
|
Sign up to set email alerts
|

Work-family conflict and job dissatisfaction among police officers: mediation of threat to family role and moderation of role segmentation enhancement

Abstract: PurposeThis study investigates the mechanism between work-family conflict (WFC) and job dissatisfaction by considering threat to family role as a mediator and role segment enhancement as a moderator.Design/methodology/approachThe data were collected from 245 male and 245 female police officers using a questionnaire-based survey method through convenience sampling.FindingsResults revealed that threat to family role partially mediates the association between WFC and job dissatisfaction. Role segment enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 49 publications
1
55
0
8
Order By: Relevance
“…Higher Education Commission of Pakistan has authorized universities that an applicant must have 16 years of education with a minimum of 2 years of work experience to be enrolled in MBA executive (which served the purpose). Second, although English is considered as the official language, still many of the employees remained unable to understand English ( Raja et al, 2004 ; Islam et al, 2019 , 2020a , b ), thus educated people were selected as they can better respond to the questionnaires in English. Finally, during the lockdown, data collection was difficult in real settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher Education Commission of Pakistan has authorized universities that an applicant must have 16 years of education with a minimum of 2 years of work experience to be enrolled in MBA executive (which served the purpose). Second, although English is considered as the official language, still many of the employees remained unable to understand English ( Raja et al, 2004 ; Islam et al, 2019 , 2020a , b ), thus educated people were selected as they can better respond to the questionnaires in English. Finally, during the lockdown, data collection was difficult in real settings.…”
Section: Methodsmentioning
confidence: 99%
“…We consider age, gender, qualification, and sector as control variables as these can have effects on respondents’ attitudes and behaviors ( Davis et al, 2019 ; Ahmad et al, 2020 ). According to gender, 84.5% ( n = 328) of the respondents were male and 15.5% ( n = 60) of the respondents were female, which represent the male-dominant culture of the country ( Islam et al, 2020b ). According to age, 46.4% ( n = 180) of the respondents were between 31 and 40 years, 35.6% ( n = 138) were less than 30 years, 12.4% ( n = 48) were between 41 and 50 years, and only 5.7% ( n = 22) were above the age of 50 years.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmad and Islam's (2019) study with Pakistani police demonstrated that perceptions of "job embeddedness" and "community embeddedness" ameliorated the negative linkage between WFC/FWC and job satisfaction. Employing the same sample, Islam et al (2020) explained the mechanisms linking WFC with job dissatisfaction through "threat to family role" and WFC/FWC with turnover intent via work engagement. Furthermore, "person-job fit" (compatibility between individuals and their jobs) buffered the negative connection between WFC/FWC and work engagement.…”
Section: Work-family Studies In Policementioning
confidence: 99%
“…Past research informs that spending time and effort for work without being able to gratify work role results in strain (Lu and Chang, 2014). The police job demands more time and effort but officers do not receive corresponding respect and recognition that creates strain (Islam et al, 2020;Rathi and Barath, 2013). Additionally, collectivist cultures value family life more than work-life (Grahame, 2003).…”
Section: Work-family Interface and Psychological Healthmentioning
confidence: 99%
“…Suifan et al (2016) investigated that the organizations which help their employees in maintaining work-life balance have paramount job and individual outcomes. Additionally scholars found that when high work demands interferes with family obligations and when remain unmonitored for longer periods of time, it creates job dissatisfaction (Islam et al, 2020). Hämmig, Knecht, Läubli, & Bauer (2011) uncovered that fulfillment of work and a family responsibility is a significant segment of worker's job satisfaction.…”
Section: Work -Family Conflict and Job Satisfactionmentioning
confidence: 99%